Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Pasien Rawat Jalan Poli Jantung di RSU Al-Islam H. M. Mawardi Krian Sidoarjo - Is Fadhillah; Dwi Ayu Lestari (Jurnal Simki Economic, 2023)
Given the intense competition in the health industry, especially hospitals, affecting the potential for hospitals to become quiet due to non-optimal service, it is necessary to conduct research related to the elements that exist in hospital services including service quality facilities, and hospital patient satisfaction. So that researchers are interested in conducting research on the effect of service quality and facilities on satisfaction of outpatients at the cardiac polyclinic at Al-Islam Hospital H. M. Mawardi Krian Sidoarjo. This study aims to determine the effect of Service Quality and Facilities on Patient Satisfaction at H. M. Mawardi Krian Sidoarjo Al-Islam Public Hospital. The design in this study uses quantitative methods. Testing the research hypothesis was carried out using the Structural Equation Modeling (SEM) approach using AMOS version 21. After analyzing the data on the suitability of the model using the Regression Weight, Confirmatory Factor Analysis (CFA) and SEM criteria approaches, the following results were obtained: Quality of Service and facilities have a simultaneous effect on satisfaction at Al-Islam Hospital H. M. Mawardi Krian Sidoarjo which obtained a P value below 0.05. This proves that the best service must be supported by the provision of adequate facilities and infrastructure. The latest technology and updates to hospital facilities also affect the quality of services available at the hospital.